On the origin of optical rotation changes during the κ-carrageenan disorder-to-order transition - Westberry BP; Rio M; Waterland MR; Williams MAK (Elsevier Ltd., 2024)
It is well established that solutions of both polymeric and oligomeric κ-carrageenan exhibit a clear change in optical rotation (OR), in concert with gel-formation for polymeric samples, as the solution is cooled in the presence of certain ions. The canonical interpretation - that this OR change reflects a 'coil-to-helix transition' in single chains - has seemed unambiguous; the solution- or 'disordered'-state structure has ubiquitously been assumed to be a 'random coil', and the helical nature of carrageenan in the solid-state was settled in the 1970s. However, recent work has found that κ-carrageenan contains substantial helical secondary structure elements in the disordered-state, raising doubts over the validity of this interpretation. To investigate the origins of the OR, density-functional theory calculations were conducted using atomic models of κ-carrageenan oligomers. Changes were found to occur in the predicted OR owing purely to dimerization of chains, and - together with the additional effects of slight changes in conformation that occur when separated helical chains form double-helices - the predicted OR changes are qualitatively consistent with experimental results. These findings contribute to a growing body of evidence that the carrageenan 'disorder-to-order' transition is a cooperative process, and have further implications for the interpretation of OR changes demonstrated by macromolecules in general.
Keywords: Carrageenan; Density-functional theory; Machine learning; Molecular dynamics; Optical rotation